Propuesta de un diseño de mejoramiento por procesos en el área comercial del Terminal Terrestre Quitumbe en el Distrito Metropolitano de Quito. - Chantera Niaupari, Paulina Elizabeth (2014)
In the city of Quito in the year 2002 was built the Terminal Terrestre Quitumbe, in order to change the old bus station Cumandá, a very ambitious project, inside there are different areas; but the principal handles the commercial area, which is responsible for providing products and services for domestic and foreign tourists. Within this area, attention to domestic and foreign tourists is the primary activity, so traders strive to provide good service is according to the requirements of customers; traders are people who hold empirical knowledge when preparing the different products that are sold in that area. It is public knowledge infrastructure of the commercial area does not help traders earn higher incomes, because that is not according to the requirements of users, and indeed, even the user directly through the commercial area.